Root coverage stability with acellular dermal matrix in multiple gingival recessions in esthetic zone: A clinical case report with 12-year follow-up - Ísis De Fátima Balderrama; Rafael Ferreira; Daniel Romeu Benchimol Rezende; Ana Lúcia Raphaelli Nahás Nogueira; Sebastião Luiz Aguiar Greghi; Mariana Schutzer Ragghianti Zangrando (Wolters Kluwer Medknow Publications, 2019)
The importance of surgical intervention for the maintenance of long-term results by root coverage of multiple gingival recessions in an esthetic area treated with a tissue substitute (acellular dermal matrix [ADM]-Alloderm®) is widely required. The present case report highlights the effectiveness of the ADM for the treatment of multiple recession defects in a female patient with Class I and II gingival recession in relation to maxillary anterior associated with esthetics and dentin hypersensitivity demands. The root coverage rate for the anterior area showed greater value with 70% of coverage; at 90 days and 2 and 12 years of follow-up, it showed 70.5%, 79%, and 77%, respectively. Conversely, for the posterior area, these rates were 68.5%, 63%, and 57% for the same follow-up periods. Results regarding gain of keratinized tissue demonstrated superior values for the anterior area, namely 3.92, 3.34 and 3.22 mm at 90 days and 2 and 12 years. These values for the posterior area were 0.54 mm, 2.41, and 1.87 mm, respectively. These findings suggest that the tissue substitute Alloderm® showed excellent long-term results for areas of multiple recessions, providing root coverage and stability of keratinized tissue gain. After this long period of evaluation, some local factors associated with recurrence of gingival recessions were detected, and a lack of proper periodontal maintenance care was observed. However, esthetic and functional outcomes achieved with surgical procedure were maintained.